Contemplating Dichotomous Nature of Gamma Delta T Cells for Immunotherapy - Bhat, Jaydeep; Placek, Katarzyna; Faissner, Simon (Frontiers in Immunology, 2022)
gd T cells are unconventional T cells, distinguished from ab T cells in a number of functional properties. Being small in number compared to ab T cells, gd T cells have managed to surprised us with their pleiotropic roles in various diseases. gd T cells are very ambiguous in nature as they can produce a number of cytokines depending on the (micro) environmental cues and engage different immune response mechanisms, mainly due to their epigenetic plasticity. Additionally, gd T cells are differentially implicated in various diseases. Depending on the disease condition, gd T cells contribute to beneficial or detrimental response. In this mini-review, we thus discuss the dichotomous nature of gd T cells in cancer, neuroimmunology and infectious diseases. We shed light on the importance of equal consideration for systems immunology and personalized approaches, as exemplified by changes in metabolic requirements. While providing the status of immunotherapy, we will assess entangle the metabolic (and other) considerations for better outcome of gd T cell-based treatments.